PENGARUH DIAMETER POHON DAN JARAK LUBANG INOKULASI TERHADAP PEMBENTUKAN GUBAL GAHARU PADA TANAMAN Aquilaria Malaccensis Lamk - Lisa, Fransiska Yesu; Muin, Abdurrani; Idham, M (Universitas Tanjungpura, 2017)
Agarwood is non-timber forest product which has high economic values, as raw material for the perfume industry, incense and medicine. This research aims to determine the best diameter of tree and inoculation hole distance to formation of gubal agarwoodÂ of Aquilaria malaccensis. The research had been conducted in Ngarak Village of Mandor Subdistrict, Landak Regency, in a periode of 3 months. The research method used factorial experiment with 5 replications. The first factor is diameter of tree with 6 treatments (17 cm, 18 cm, 21 cm, 23 cm. 24 cm and 27 cm). The second factor is distance of inoculation holes (5 cm, 10 cm, 15 cm, 20 cm, 25 cm and 30 cm). the data collected were in the form of cross-sectional area of agarwood formed the results showed that the interaction of tree diameter ofÂ 3,86 with a inoculation hole spacing of 5cm was the best for the formation of the gubal agarwood compared to other treatments. Keywords: Aquilaria malaccensis, Gubal Agarwood, Inoculation, Tree Diameter.